Fabrication of a Flexible Aqueous Textile Zinc-Ion Battery in a Single Fabric Layer - Yong, Sheng; Hillier, Nicholas; Beeby, Stephen (Frontiers in Electronics, 2022)
Zinc-ion batteries (ZIB), with various manganese oxide-based cathodes, provide a promising solution for textile-based flexible energy storage devices. This paper demonstrates, for the first time, an aqueous ZIB fabricated in a single woven polyester cotton textile. The textile was functionalized with a flexible polymer membrane layer that fills the gaps between textile yarns, enabling fine control over the depth of penetration of the spray deposited manganese oxide cathode and zinc anode. This leaves an uncoated region in the textile-polymer network that acts as the battery’s separator. The textile battery cell was vacuum impregnated with the aqueous electrolyte, achieving good wettability of the electrodes with the electrolyte. Additionally, the choice of cathodic material and its influence over the electrochemical performance of the zinc ion battery was investigated with commercially available Manganese (IV) oxide and Manganese (II, III) oxide. The textile ZIB with Manganese (II, III) oxide cathode (10.9 mAh.g-1 or 35.6 µAh.cm-2) achieved better performance than the textile ZIB with Manganese (IV) oxide (8.95 mAh.g-1 or 24.2 µAh.cm-2) at 1 mA.cm-2 (0.3A.g-1). This work presents a novel all-textile battery architecture and demonstrates the capability of using manganese oxides as cathodes for a full textile-based flexible aqueous ZIB.